Addition of a fracture risk assessment to a coordinator's role improved treatment rates within 6 months of screening in a fragility fracture screening program. Issue 3 (March 2017) - Beaton, D.; Vidmar, M.; Pitzul, K.; Sujic, R.; Rotondi, N.; Bogoch, E.; Sale, J.; Jain, R.; Weldon, J.
Abstract Summary We evaluated the impact of a more intensive version of an existing post-fracture coordinator-based fracture prevention program and found that the addition of a full-risk assessment improved treatment rates. These findings provide additional support for more intensive programs aimed at reducing the risk of re-fractures. Introduction Evidence-based guidelines support coordinator-based programs to improve post-fracture osteoporosis guideline uptake, with more intensive programs including bone mineral density (BMD) testing and/or treatment being associated with better patient outcomes. The purpose of this study was to evaluate the impact of a more intensive version (BMD "fast track") of an existing provincial coordinator-based program. Methods We compared two versions of the program that screened treatment naïve fragility fracture patients (>50 years). Cases came from the BMD fast track program that included full fracture risk assessment and communication of relevant guidelines to the primary care provider (PCP). Matched controls were selected from the usual care program matching according to age, sex, fracture type, and date. Two matching techniques were used: traditional (hard) matching (TM) and propensity score matching (PS). The outcomes were treatment initiation with bone sparing medication, BMD testing rate, and the rate of returning to discuss the test results with a PCP. Results The program improvements led to a significant improvement in treatment initiation within 6 months from 16 % (controls based on PS) or 21 % (controls based on TM) to 32 % (cases). Ninety percent of patients in the BMD fast track program returned to their PCP to discuss bone health in the cases versus 60 % of the controls (for TM and PS). BMD testing occurred in 96 % of cases compared to the 66 (TM) or 65 % (PS) of the matched controls. Conclusions Addition of a full-risk assessment to a coordinator-based program significantly improved treatment rates within 6 months of screening.